Managing emotions while working from home during COVID-19 pandemic: working mothers with young children perspective / Tengku Elena Tengku Mahamad ... [et al.] - Tengku Mahamad, Tengku Elena; Abdul Ghani, Wan Soraya Wan; De Luna, Daina Bellido; Rivadeneira, Lucia (2021)
The struggle to balance work and family can be a major stressor for women with young children as it can negatively influence their emotional well-being. Studies have found that employed women experience greater difficulty than men in balancing between work and family as they have greater demands. Besides that, women tend to experience low psychological detachment from work while at home, and the emotions they experience at home have negative implications for their work engagement. This study aimed to investigate how working mothers with young children between 0 to 5 years old regulate their work-generated emotions while working from home during the coronavirus (COVID-19) pandemic. The pandemic forced workers to work from home to curb transmission of the virus. By utilizing the qualitative research method, this study gathered the perspectives of 20 Malaysian working mothers from various public and private organizations who were required to work from home due to the pandemic. They were chosen by using the purposive sampling method, and all transcribed interviews were coded thematically. Qualitative analyses revealed that working mothers often find it difficult to manage their emotions while attempting to balance childcare and work. Some discussed the possible problematic outcomes caused by working from homes, such as stress, anxiety, and social isolation. We conclude that working mothers struggle emotionally when working from home and the impact can vary depending on the age of their children and, their marital status. The study provides some initial evidence that the impact of work from home with young children on emotions is worthy of further investigation.